Requirement Model of School Management System for Adult Commercial Secondary School in Somalia (ACSSMS) - Abdullahi, Hussein (2011)
To develop a system, it is necessary for the system's analyst to provide a model. In order to produce this model, the analyst must identify the user’s requirement first. Requirement model is one of the techniques used to model out the user’s requirement for a specific system before the development of that system. In other words, requirement model gives a view of the user’s requirement for a particular system. The purpose of this study is to create a requirement model as a basis to develop school management system for Adult Commercial Secondary School in Somalia. So, during this study, the UML graphical notation was used to model out the requirement model of the proposed school management system, and the requirement model was designed and presented using different UML tools (e.g., use case diagram, use case specifications, activity diagram, sequence diagram, collaboration diagram and class diagram), and supporting textual information. Also, a small prototype was then developed and presented in this study, which covers some of the main functional requirements, so as to assist the school in managing their daily operations effectively and more efficiently. Thus, this study is believed to be a step forward and very crucial guidance for Adult School in Somalia to be able to give this model to system developers to build the proposed school management system.